Standardization of Pre-sowing Seed Treatment with selected Botanical, Biofertilizers and Plant Growth Regulator on Seedling parameters of Maize (Zea mays L.) - Swapnil Budhbaware; Rai, Prashant Kumar (Journal of Cereal Research, 2023)
Maize also called as corn, botanical name (Zea mays L.) having chromosome no of 2n=20 under Poaceae family, is a widely cultivated crop that originated in the Americas. It is known for its various uses and properties. Maize is not only a staple in many cuisines around the world, but it also serves as a vital source of feed for livestock. Additionally, its versatility extends to industrials applications, including the production of biofuels. With its rich history and global significance, maize continues to captivate and nourish people worldwide. A laboratory experiment was performed in Notified State Seed Testing Laboratory, Department of Genetics and Plant Breeding, Naini Agricultural Institute, SHUATS, Prayagraj, U.P. during January to June, 2023 in which the seeds of Maize variety Early Wonder were soaked for 12 hours in the solution of Seaweed extract (0.5% and 1%), Azospirillum (10% and 20%), Pseudomonas (10% and 20%), Melatonin (50 µM and 100 µM), Gibberellic acid (50 ppm and 100 ppm) and Salicylic Acid (50 ppm and 100 ppm), respectively. The experiment was conducted in Completely Randomized Design with 4 Replication and overall and control. The results clearly revealed that all the treatments show significantly positive effect on seedling parameters as compared to control. Among all, seed priming with Azospirillum 20 % soaking seeds for 12 hrs shows significantly higher seedling parameters. As compared to Control increase in Germination percentage by (21%), speed of Germination (29), Germination index (402), shoot length (8.14 cm), root length (6.44 cm), seedling length (14.58 cm), Seedling fresh weight (4.48 gm), seedling dry weight (0.93 gm), seedling Vigour Index I (1981) and seedling Vigour Index II (119). It was concluded that Azospirillum 20 % enhances seedling parameters and significant increase in germination and vigour parameters on Maize seedlings.